Assessment of line differentiation in the Thoroughbred horse breed using DNA microsatellite loci - L. A. Khrabrova; N. V. Blohina; O. I. Suleymanov; G. А. Rozhdestvenskaya; V. F. Pustovoy (Вавиловский журнал генетики и селекции)
The Thoroughbred (TB) horse is the best racehorse breed used in the racing industry. This breed has had a closed studbook for about 300 years. In Russia TB horses have been bred since the second half of the XVIII century. The modern Russian Stud Book register of TB horses is partially presented by stallions and broodmares imported from different countries. The genealogical structure of the breed is represented by 17 lines, among which the Northern Dancer line dominates (30.9 %). The study of features of different lines of TB was carried out on 17 loci of DNA microsatellites (VHL20, HTG4, AHT4, HMS7, HTG6, AHT5, HMS6, ASB23, ASB2, HTG10, HTG7, HMS3, HMS2, ASB17, LEX3, HMS1 and CA425) to assess genetic differentiation of the genealogical structure. The results of the DNA typing of 8091 Thoroughbred horses across microsatellite loci show that the gene pool of the domestic population is represented by 100 alleles typical of the breed. A comparative analysis of the genotypes of horses representing different lines indicates that they differ in the number of alleles (85–99), allele frequencies, the level of polymorphism Ae (2.93–3.48) and the degree of the observed heterozygosity Ho (0.653–0.739). The genetic distances between the lines varied in a wide range from 0.014 (Nasrullah – Northern Dancer) to 0.125 (Massine – Teddy). The correspondence to HWE was maintained in most lines, which is confirmed by the negative values of Fis. Cluster analysis demonstrated the correspondence of the obtained dendrogram of Nei’s genetic distances to its genealogical scheme of lines. Genetic differentiation of lines by index Fst varied in a range 0.005–0.073 at the mean value Fst = 0.024. The data indicate genetic differentiation of lines of TB at the STR markers and confirm the effectiveness of the system of linear breeding for the maintenance of interbreed biodiversity.